2023
DOI: 10.1155/2023/1950257
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐ and Age‐Related Differences of Ocular Biometric Parameters in Patients Undergoing Cataract Surgery in Bosnia and Herzegovina

Edita Zvorničanin,
Zoran Vatavuk,
Maja Popović
et al.

Abstract: Purpose. The aim of the study is to determine the distribution and mutual relationship of ocular biometric parameters, as well as to evaluate gender- and age-related differences in patients undergoing cataract surgery in Bosnia and Herzegovina. Materials and Methods. It was a retrospective cross-sectional study of consecutive patients who underwent cataract surgery between January 2017 and December 2021 in a tertiary care clinic. All biometric measurements were performed using the optical biometer OA-2000 (Tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…A study in Texas showed differences in ACD among patients from Hispanic and non-Hispanic white races with cataracts, and this ethnic difference may be a risk factor for developing corneal endothelial damage after cataract surgery [16] . The research involving patients with cataracts from Bosnia and Herzegovina and India's Northeast region showed differences in AL, ACD, and keratometry between sexes [13,17] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A study in Texas showed differences in ACD among patients from Hispanic and non-Hispanic white races with cataracts, and this ethnic difference may be a risk factor for developing corneal endothelial damage after cataract surgery [16] . The research involving patients with cataracts from Bosnia and Herzegovina and India's Northeast region showed differences in AL, ACD, and keratometry between sexes [13,17] .…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, identifying these differences in ocular biometric parameters is useful for assessing the status of associated ocular diseases and guiding surgical and postoperative care. Relevant studies have been conducted in countries such as the United States, Spain, South Korea, and Bosnia and Herzegovina [9][10][11][12][13] ; however, most of them are limited to a single ethnic group in a single region. Owing to the differences in measuring instruments and patient inclusion criteria, it is difficult to compare ocular biometric parameters between ethnic groups.…”
Section: •Clinical Research•mentioning
confidence: 99%